2020
DOI: 10.1111/pcn.13078
|View full text |Cite
|
Sign up to set email alerts
|

Different serum protein factor levels in first‐episode drug‐naive patients with schizophrenia characterized by positive and negative symptoms

Abstract: Aim The clinical features of schizophrenia can be mainly divided into two symptom domains: positive and negative. Patients in each symptom domain respond differently to treatments, and their prognoses vary accordingly. Serum protein factors, such as nerve growth factor (NGF), neurotrophin‐3 (NT‐3), interleukin‐6 (IL‐6), interleukin‐1 beta (IL‐1β), and the calcium‐binding protein, S100β, have been reported to be involved in the pathogenesis of schizophrenia. However, their roles in the positive and negative sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…Specifically, acute exacerbations seem to create an increase in their values [75]. Still, other authors found a significant association between serum levels of IL-1β and negative rather than positive symptoms [76, 77]. On the other hand, an absence of correlation between psychopathology and interleukin levels has also been reported, in accordance with our data [78].…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, acute exacerbations seem to create an increase in their values [75]. Still, other authors found a significant association between serum levels of IL-1β and negative rather than positive symptoms [76, 77]. On the other hand, an absence of correlation between psychopathology and interleukin levels has also been reported, in accordance with our data [78].…”
Section: Discussionsupporting
confidence: 91%
“…23 Study on serum protein factors indicated that IL-1β expression level was positively associated with the negative symptom score of the Positive and Negative Syndrome Scale (PANSS) in SCZ patients. 24 The plasma levels of dopamine metabolites were significantly correlated with the mismatch negativity of SCZ, but not the serotonin metabolites. 25 In our previous study, we used the GC-MS based metabolomics to find out that the energy metabolism, oxidative stress, and neurotransmitter metabolism were disturbed in the peripheral blood mononuclear cells of SCZ patients.…”
Section: Introductionmentioning
confidence: 89%
“…In a recent study, researchers found that C‐reactive protein blood level was abnormally increased in non‐remission SCZ and therefore was suggested as a potential biomarker 23 . Study on serum protein factors indicated that IL‐1β expression level was positively associated with the negative symptom score of the Positive and Negative Syndrome Scale (PANSS) in SCZ patients 24 . The plasma levels of dopamine metabolites were significantly correlated with the mismatch negativity of SCZ, but not the serotonin metabolites 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a previous study has also reported that patients with negative symptoms are likely to have more serious neuroimmune disturbances. 29 One limitation of our study was that we did not further investigate the associations between CpG island methylation in the promoter region of RELN and IL-6, IL-1b, or MBP. We will study such associations in the future.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study has also reported that serum IL-1β and IL-6 levels are higher in patients with schizophrenia characterized by negative symptoms than in those characterized by positive symptoms. 29 This suggests that type II patients (with schizophrenia characterized by negative symptoms) have more severe neuroimmune and nerve damage.…”
Section: Discussionmentioning
confidence: 99%